New Conjugated Benzothiazole-N-oxides: Synthesis and Biological Activity - Gajdoš, Peter (Molecules, 2009)
Eleven new 2-styrylbenzothiazole-N-oxides have been prepared by aldol – type condensation reactions between 2-methylbenzothiazole–N-oxide and para-substituted benzaldehydes. Compounds with cyclic amino substituents showed typical push-pull molecule properties. Four compounds were tested against various bacterial strains as well as the protozoan Euglena gracilis as model microorganisms. Unlike previously prepared analogous benzothiazolium salts, only weak activity was recorded.